2020
DOI: 10.1021/acs.jchemed.0c00645
|View full text |Cite
|
Sign up to set email alerts
|

Online Chemistry Crossword Puzzles prior to and during COVID-19: Light-Hearted Revision Aids That Work

Abstract: This work explores the performance of online postlecture chemistry crossword puzzles as revision aids for 132 first-year and 120 second-year undergraduate pharmacy students. The use of these puzzles as a form of remote active learning was fortuitously evaluated immediately prior to and during the COVID-19 pandemic based on students' online study behavior patterns, which captured some fascinating data on the frequency and timing of student online viewings. Students' anonymous feedback responses were also evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
(81 reference statements)
0
19
0
Order By: Relevance
“…In the case of da Silva et al ( 2021), 44 pharmacy undergraduate students were included. In the studies done by D'Angelo (2020) and Fontana (2020), all the students belonged to the same classroom, whereas 132 first-year and 120 second-year undergraduate pharmacy students participated in the study of Pearson (2020). Nevertheless, the main weakness comes from the predominant use of subjective procedures to assess learning outcomes.…”
Section: Chemistry Learningmentioning
confidence: 99%
“…In the case of da Silva et al ( 2021), 44 pharmacy undergraduate students were included. In the studies done by D'Angelo (2020) and Fontana (2020), all the students belonged to the same classroom, whereas 132 first-year and 120 second-year undergraduate pharmacy students participated in the study of Pearson (2020). Nevertheless, the main weakness comes from the predominant use of subjective procedures to assess learning outcomes.…”
Section: Chemistry Learningmentioning
confidence: 99%
“…Similarly, only around half of the pharmacy students (or a slightly more than half of the students in some cases) manifested positive perceptions on specific online courses during the COVID-19 pandemic (e.g., an anatomy and histology course; a virtual microbiology simulation; chemistry crossword puzzles as revision aids) [7,[44][45][46]. Moreover, students' understanding may have been affected in one study [7], and knowledge acquisition was not statistically different between both settings (i.e., in-person vs. online education) in another study [43].…”
Section: Studies Related To the Involvement Of Pharmacy Students In S...mentioning
confidence: 99%
“…In the paper by Pearson (2002), the authors examined the use of crossword puzzles after a distance lecture during the Covid-19 pandemic to help revise chemistry material in first-and second-year students. The results showed that students accepted crossword puzzles as a form of active learning, that they found them useful and that it was desirable to apply them more in teaching (Pearson, 2020).…”
Section: Chemistry Education During the Covid-19 Pandemicmentioning
confidence: 99%